Economic analysis of subsistence agriculture in García Rovira, Colombia - Londoño Ríos, Diego (Universidad de Caldas, 1975)
The major objectives of this study were to: (1) describe the main agricultural and livestock activities carried out by farmers., the types of technology beíng used, and the prevail- ing management systems, (2) delineate the resources available to farmers, (3) analyze patterns of resource allocatlon and the associated productivity, and income levels obtained by farmers, (4) identify factors related to poverty and suggest ways to alleviate it, and (5) propose strategies leading to the achievement of the goals established for the regional development project. USing information gathered from a sample of farms, functional relationships among economic variables were determined, and the kind of resourses available to farmers were described as well as the types of technology, and management systems under which the produc- tion process took place. Input-output coefficients were estimated by least squares miltiple regression procedures from three aggregate, and seven individual enterprise Cobb-Doug1as production function models, and the efficiency of resource a11ocation and product mi x on farms were j udged. Fi na 11y, respondents of the survey were divided into two subgroups based on whether or not their reported annua1 gross income was $15,000 pesos or more.